PEMANFAATAN MICROSOFT EXCEL UNTUK PEMBELAJARAN MATEMATIKA DAN GRAFIK - Harmastuti -; Dwi Setyowati (LPPM IST AKPRIND Yogyakarta, 2018)
Mathematics is a study studying the operation of numbers, functions, graphs, space and in the learning can be delivered manually and visually can be used computer. To answer that Microsoft excel is an alternative software part of Microsoft Office can be used to help solve problems related to mathematical modeling, real-time and graphical visual operations of a mathematical function or group of data. In this community service activity was introduced the use of Microsoft excel to complete mathematical operations or mathematical modeling and graphical visuals according to the given module. Results from community service activities students are enthusiastic in practicing the operation of numbers, also create graphical visuals using Microsoft Excel.